2007
DOI: 10.3201/eid1309.060774
|View full text |Cite
|
Sign up to set email alerts
|

HIV and Tuberculosis in Ho Chi Minh City, Vietnam, 1997–2002

Abstract: An emerging HIV epidemic, concentrated in young, male, injection drug users, is responsible for increasing TB reporting rates in urban Vietnam.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 24 publications
1
8
0
Order By: Relevance
“…Further studies are needed to identify the prevalence of HIV and tuberculosis co-infection in the population and its significance for the total burden of tuberculosis in Viet Nam, because the increasing prevalence of HIV infection in parts of Viet Nam may have increased the burden of HIV and tuberculosis co-infection. 24 The results of this first national prevalence survey showed a prevalence of tuberculosis in Viet Nam that was 1.6 times as high as previously estimated. A significant number of tuberculosis smearpositive and smear-negative cases remain undiagnosed and present a potential source of transmission in the community.…”
Section: Nguyen Binh Hoa Et Al Tuberculosis Prevalence Survey In Viesupporting
confidence: 65%
“…Further studies are needed to identify the prevalence of HIV and tuberculosis co-infection in the population and its significance for the total burden of tuberculosis in Viet Nam, because the increasing prevalence of HIV infection in parts of Viet Nam may have increased the burden of HIV and tuberculosis co-infection. 24 The results of this first national prevalence survey showed a prevalence of tuberculosis in Viet Nam that was 1.6 times as high as previously estimated. A significant number of tuberculosis smearpositive and smear-negative cases remain undiagnosed and present a potential source of transmission in the community.…”
Section: Nguyen Binh Hoa Et Al Tuberculosis Prevalence Survey In Viesupporting
confidence: 65%
“…One province in Cambodia reported that 38% of TB patients were HIV‐positive, and 28% of the people living with HIV had active TB 38 . A similar concentration of HIV infection is seen in China and in Vietnam 39,40 . The problem is also considerable in Malaysia 41,42 as well as in Singapore (seropositivity among TB patients is 1.3%) 37 .…”
Section: Coinfection With Hiv/aidsmentioning
confidence: 65%
“…38 A similar concentration of HIV infection is seen in China and in Vietnam. 39,40 The problem is also considerable in Malaysia 41,42 as well as in Singapore (seropositivity among TB patients is 1.3%). 37 In other countries or areas, the problem remains rather sporadic at the moment, but in some countries, as in Japan, HIV infection continues to spread steadily and insidiously, so the problem will become serious unless it is addressed more properly by both HIV/ AIDS and TB medical professionals.…”
Section: Coinfection With Hiv/aidsmentioning
confidence: 99%
“…The emerging HIV epidemic was one of these risk factors. Research indicated that, in high HIV prevalence areas, it is only partly responsible for this increase [13,14].…”
Section: Technical Assistance Provided By Kncvmentioning
confidence: 99%